Citizens' Environmental Study Committee Meeting Briefing Report with Reports on Noise Pollution - Jane Tolmach::::::; Robert Brown::::::; Elizabeth Cuadra:::::: (1970)
A memorandum informing city council of the items discussed at a meeting on a proposed airport in Oxnard, California. Includes two reports presented on noise pollution that would be caused by said proposed airport.